The Laccase‐Lig Multienzymatic Multistep System in Lignin Valorization. Issue 20 (2nd September 2022) - Vignali, Elisa; Gigli, Matteo; Cailotto, Simone; Pollegioni, Loredano; Rosini, Elena; Crestini, Claudia
Abstract: A laccase‐Lig multienzymatic multistep system for lignin depolymerization was designed and developed. Studies were performed on pristine and fractionated lignins (Kraft and Organosolv) using a specific cascade of enzymes, that is, laccases from Bacillus licheniformis and from Funalia trogii, respectively for Kraft and Organosolv lignin, followed by the Lig system from Sphingobium sp. SYK‐6 (β‐etherases Lig E and Lig F, glutathione lyase Lig G). Careful elucidation of the structural modifications occurring in the residual lignins associated with the identification and quantification of the generated low‐molecular‐weight compounds showed that (i) the laccase‐Lig system cleaves non‐phenolic aryl glycerol β‐O‐4 aryl ether bonds, and (ii) the overall reactivity is heavily dependent on the individual lignin structure. More specifically, samples with low phenolic/aliphatic OH groups ratio undergo net depolymerization, while an increased phenolic/aliphatic OH ratio results in the polymerization of the residual lignin irrespective of its botanical origin and isolation process. Abstract : Multistep catalysis : The ratio between phenolic and aliphatic OH groups plays a crucial role in determining the overall reactivity towards the cleavage of non‐phenolic aryl glycerol β‐O‐4 aryl ether bonds of lignin by the Laccase‐Lig multistep catalytic system. Lignin samples showing low phenolic/aliphatic OH ratio undergo net depolymerization, while a higher phenolic/aliphatic OH ratio results in the polymerization of the residual lignin irrespective of its origin.